PENGARUH HARGA DAN WORD OF MOUTH (WOM) TERHADAP MINAT BELI LAPTOP MEREK TOSHIBA DIKALANGAN MAHASISWA UNIVERSITAS NEGERI PADANG - Septi Ayu Lestari; Rose Rahmidani (Universitas Negeri Padang, 2019)
This study aims to know and prove how much the effect of Price and Word Of Mouth On The Purchase Intention Toshiba Brand Laptops Among Students From Padang State University. This type of research is causative. The population in this Students from Padang State University. The samples were taken using Cochran formula with 100 respondents. This sampling technique is based on non- probability sampling method. The type of data used in this study primary data. Data analysis technique using SPSS version 21.00. the result of this study indicate that: 1) Price has a positive significant effect on purchase intention, 2) Word of Mouth has a positive significant effect on purchase intention.Keywords: Price, Word of Mouth, Purchase Intention